Global spread of wheat curl mite by its most polyphagous and pestiferous lineages. (13th May 2014) - Skoracka, A.; Rector, B.; Kuczyński, L.; Szydło, W.; Hein, G.; French, R.
Abstract The wheat curl mite (WCM), Aceria tosichella, is an important pest of wheat and other cereal crops that transmits wheat streak mosaic virus and several other plant viruses. Wheat curl mite has long been considered a single polyphagous species, but recent studies in Poland revealed a complex of genetically distinct lineages with divergent host‐acceptance traits, ranging from highly polyphagous to host‐specific. This diversity of WCM genotypes and host‐acceptance phenotypes in Europe, the presumed native range of WCM, raises questions about the lineage identities of invasive WCM populations on other continents and their relationships to European lineages. The goals of this study were to examine the global presence of WCM and determine the relatedness of lineages established in different continents, on the basis of phylogenetic analyses of mitochondrial and nuclear DNA sequence data. Host‐range bioassays of a highly polyphagous WCM lineage were performed to supplement existing data on this lineage's ability to colonise graminaceous and non‐graminaceous hosts. Invasive WCM populations in North and South America and Australia assorted with the only three known polyphagous and pestiferous WCM lineages ('MT‐1', 'MT‐7' and 'MT‐8') from a total of eight currently described lineages. These results show that the most polyphagous lineages were more successful colonisers and reflect a need for extensive surveys for WCM on both crops and wild grass species in invaded continents. The most invasive lineage ('MT‐1') was shown to successfully colonise all 10 plant species tested in three families and has spread to North and South America and Australia from its presumed origins in Eurasia.